A High-Status Middle Sarmatian Burial from the Kovalevka Burial Complex in the Volgograd Region - Valeriy M. Klepikov (Нижневолжский археологический вестник)
The article is devoted to the archaeological materials publication from the kurgan 25 excavations of the Kovalevka burial complex. The accompanying inventory, marking a high status of the buried, was found in an individual burial made in the tradition of the Middle Sarmatian funeral rite. The bronze cauldron broken in antiquity and placed upside down was found in the cache. Cauldrons of this type existed in the first century AD. Iron bits with two-hole psalms, widespread among the nomads of the steppe zone starting from the turn of the eras and silver-plated iron plaques from the horse bridle jewelry lay nearby. The set of three phalars, which can be functionally defined as breast and shoulder plates of a horse harness, was found on the other side of the cauldron. The phalars made of forged silver sheet traces of gilding on the surface. The multi-figure compositions of animals, birds and floral ornaments were depicted on the obverse, in low relief. Such phalars in Sarmatian monuments were widespread since the turn of the era and exist within the first half of the first century AD. On both sides of the cauldron there were two gray-clay pottery jugs made in Kuban pottery centers. They became widespread in the burial grounds of the Kuban and the Lower Don starting from the turn of the eras, although they were occasionally encountered at the end of the Early Sarmatian time. Two paired long militant knives were placed along the right leg; these finds are well known in the Sarmatian burials of the turn of the first centuries AD, and are found, as a rule, in high status complexes along with horse harness, bronze cauldrons and other prestigious items. All of the above allows us to assert that the buried individual belonged to the nomadic elite, whose burials during that period were concentrated in the Volga-Don interfluve.